2011
DOI: 10.1016/j.neuron.2011.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Dephosphorylation of Dynamin1 by Calcineurin Couples Neurotrophin Receptor Endocytosis to Axonal Growth

Abstract: Summary Endocytic events are critical for neuronal survival in response to target-derived neurotrophic cues, but whether local axon growth is mediated by endocytosis-dependent signaling mechanisms remains unclear. Here, we report that Nerve Growth Factor (NGF) promotes endocytosis of its TrkA receptors and axon growth by calcineurin-mediated dephosphorylation of the endocytic GTPase, dynamin1. Conditional deletion of calcineurin in sympathetic neurons disrupts NGF-dependent innervation of peripheral target tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 45 publications
(68 reference statements)
8
90
0
Order By: Relevance
“…It is interesting to note that synapsin 1 KO synapses have enhanced paired-pulse facilitation reminiscent of what we have observed in dynamin DKO synapses (86), raising the possibility that a chronic dissociation of synapsin 1 from the vesicles may play a role in such facilitation at DKO synapses. Whether the Ca 2+ -dependent phosphatase calcineurin, which plays an important role in the Ca 2+ -dependent dephosphorylation of several endocytic proteins including dynamin and directly binds the dynamin 1b splice variant (87,88), is implicated in these changes remains an interesting question to address in future studies. Neither sites 1 and 2 of synapsin 1 nor threonine 286 of CaMKII are dephosphorylated by calcineurin, but the phosphorylation state of these sites could be controlled by dephosphorylation cascades triggered by calcineurin (89, 90).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that synapsin 1 KO synapses have enhanced paired-pulse facilitation reminiscent of what we have observed in dynamin DKO synapses (86), raising the possibility that a chronic dissociation of synapsin 1 from the vesicles may play a role in such facilitation at DKO synapses. Whether the Ca 2+ -dependent phosphatase calcineurin, which plays an important role in the Ca 2+ -dependent dephosphorylation of several endocytic proteins including dynamin and directly binds the dynamin 1b splice variant (87,88), is implicated in these changes remains an interesting question to address in future studies. Neither sites 1 and 2 of synapsin 1 nor threonine 286 of CaMKII are dephosphorylated by calcineurin, but the phosphorylation state of these sites could be controlled by dephosphorylation cascades triggered by calcineurin (89, 90).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Kuruvilla and colleagues showed that in sympathetic neurons, NGF activation of TrkA results in IP3-induced Ca 2þ release and the subsequent activation of the calcium-responsive phosphatase calcineurin ( Fig. 2B) (Bodmer et al 2011). Surprisingly, calcineurin selectively interacts with and dephosphorylates the neuron-specific splice variant of dynamin (dynamin1).…”
Section: Signaling Propertiesmentioning
confidence: 91%
“…TrkA signaling that is induced by NT3 elicits local signaling that is important for the finding of intermediate targets (e.g. axon extension along the vasculature) (Ascano et al, 2012;Bodmer et al, 2011). By contrast, TrkA signaling that is induced by NGF results in its retrograde transport and the activation of calcineurin (a phosphatase that dephosphorylates the transcription factor NFAT), leading to NFAT-mediated transcriptional control of growth-promoting genes (Ascano et al, 2012;Bodmer et al, 2011).…”
Section: Nt3mentioning
confidence: 99%
“…axon extension along the vasculature) (Ascano et al, 2012;Bodmer et al, 2011). By contrast, TrkA signaling that is induced by NGF results in its retrograde transport and the activation of calcineurin (a phosphatase that dephosphorylates the transcription factor NFAT), leading to NFAT-mediated transcriptional control of growth-promoting genes (Ascano et al, 2012;Bodmer et al, 2011). Interestingly, a proteomic approach (Harrington et al, 2011) has identified the differential recruitment of actin modifiers to endosomes containing either NGF-TrkA or NT3-TrkA; the association of Rac1 and cofilin proteins, which occurs exclusively at NGF-TrkA-containing endosomes, is essential for the maturation of early-to-late endosomes that are competent for retrograde transport.…”
Section: Nt3mentioning
confidence: 99%